PENGARUH PROFITABILITAS DAN BIAYA OPERASIONAL TERHADAP PPh BADAN PERUSAHAAN MAKANAN DAN MINUMAN DI BEI (PERIODE 2013 – 2015) - Indri Atina, Fadjar Harimurti & Djoko Kristianto (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
The purpose of this study to determine the significance of the effect of the netprofit margin and operating expenses to the corporate income tax. The population inthis study is a food and beverage company listed in Indonesia Stock Exchange in2013-2015. Sampling techniques in this study using purposive sampling in order toobtain a sample of 11 companies out of 15 companies that meet the criteria of foodand beverage companies in the Indonesia Stock Exchange in the years 2013-2015.Data taken from the official website of Indonesia Stock Exchange (www.idx.co.id).The results of t test analysis showed that there was no significant effect on the netprofit margin of the corporate income tax, a significant influence on the operationalcosts of the corporate income tax. F test results indicate that a significant differencebetween the net profit margin and operating expenses to the corporate income tax.Keywords: net profit margin, operating expenses, corporate income tax